Compositions for Limestone Restoration - Burakov, Vladimir V.; Loganina, Valentina; Zaytseva, Mariya (International Journal of Architectural Engineering Technology, 2022)
Information about the lime composition used for the restoration of limestone is given. It has been shown that using a polysilicate mortar to formulate a lime composition contributes to an increase in water resistance, adhesion strength of the composition to the base, and acceleration of curing. A primer composition is proposed, including liquid sodium glass and calcium chloride.